2015
DOI: 10.1186/s12910-015-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting professional ethics in nursing practice in Iran: a qualitative study

Abstract: BackgroundProfessional ethics refers to the use of logical and consistent communication, knowledge, clinical skills, emotions and values in nursing practice. This study aimed to explore and describe factors that affect professional ethics in nursing practice in Iran.MethodsThis qualitative study was conducted using conventional content analysis approach. Thirty nurses with at least 5 years of experience participated in the study; they were selected using purposive sampling. Data were collected through semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 27 publications
1
102
0
11
Order By: Relevance
“…[5] Values form a framework for addressing ethical concerns [6] and are translated as personal principles or standards of behaviour displayed by an individual. [7,8] Similarly, professional values are important concepts that integrate the students' critical thinking as well as the moral and ethical skills needed to deliver competent nursing care. [8] Professional values are reflections of personal values [6] and are acquired during socialization into nursing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Values form a framework for addressing ethical concerns [6] and are translated as personal principles or standards of behaviour displayed by an individual. [7,8] Similarly, professional values are important concepts that integrate the students' critical thinking as well as the moral and ethical skills needed to deliver competent nursing care. [8] Professional values are reflections of personal values [6] and are acquired during socialization into nursing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[7,8] Similarly, professional values are important concepts that integrate the students' critical thinking as well as the moral and ethical skills needed to deliver competent nursing care. [8] Professional values are reflections of personal values [6] and are acquired during socialization into nursing. Globally, professional values in nursing has been described using varying characteristics, which, when translated, are fundamentally the same.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study indicated a significant positive correlation between nurses' moral sensitivity and patients' satisfaction with the quality of nursing care. In explaining such finding, it can be said that moral sensitivity may increase the ability to communicate effectively and professionally, empathy, accountability and improve the quality of nurses' working life [18,21,[24][25][26] and increase patients' satisfaction through improving nursing care behaviors [27].…”
Section: Discussionmentioning
confidence: 99%
“…A Dehghani i wsp. [22] stwierdzili, że większość respondentów uważa, że szkolenia w zakresie etyki są bardzo potrzebne. Według innych badań ankietowani uzyskują wiedzę z innych źródeł.…”
Section: Dyskusjaunclassified